Carbon dioxide adsorption material as well as preparation method and application thereof

By introducing organic amines, surfactants and nanooxides in the preparation process of the aerogel, the modified phenolic resin and modified gel are formed, and the problems of volume shrinkage and structural deterioration during the atmospheric drying process are solved, and efficient carbon dioxide adsorption performance and low-cost production are achieved.

CN119909660APending Publication Date: 2025-05-02JIANGSU SUJING GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510281650.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the drying process of normal pressure, existing aerogels are prone to volume shrinkage and structural deterioration, resulting in a degradation of adsorption performance.

Method used

By adding organic amines and surfactants to the polycondensation reaction of aminophenol and aldehydes, and introducing nanooxides with surface hydroxyl groups during the gelation process, a modified phenolic resin sol and a modified gel are formed, and carbon dioxide adsorption material is obtained by solvent replacement and atmospheric pressure drying.

Benefits of technology

It significantly reduces the volume shrinkage of the aerogel material, maintains the stability of the pore structure, improves the adsorption performance of carbon dioxide, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909660A_ABST
    Figure CN119909660A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dioxide adsorption material and a preparation method and application thereof.The preparation method comprises the steps that in the presence of a surfactant, aminophenol and aldehyde are subjected to a condensation polymerization reaction in an alcohol-water mixed system, organic amine is added in the condensation polymerization reaction process, a reaction is conducted, and modified phenolic resin sol is prepared; adding nano oxide with surface hydroxyl into the modified phenolic resin sol, uniformly dispersing, and aging under a heating condition to prepare modified gel; carrying out solvent replacement on the modified gel in the aging solution to obtain aged gel, and drying the aged gel to obtain the carbon dioxide adsorption material. According to the method disclosed by the invention, the volume shrinkage of the aerogel material can be obviously reduced when normal-pressure drying is adopted, the problem that the gel prepared by the existing method is easy to collapse in structure and the like when being dried at normal pressure can be avoided, and better adsorption performance and the like are taken into account while the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a carbon dioxide adsorption material and a preparation method and application thereof. Background Art

[0002] In order to cope with climate change, the International Energy Agency (IEA) has proposed carbon dioxide capture and storage technology (CCS) and carbon dioxide capture and utilization technology (CCU). The main capture methods currently include pre-combustion capture, post-combustion capture and oxygen-enriched combustion capture, among which post-combustion capture is the most widely used, including absorption, cryogenic separation, membrane separation and adsorption. Although alcohol amine liquid absorbents have a large adsorption capacity, there are problems of equipment corrosion and difficulty in recovery; cryogenic separation is only applicable to high-concentration carbon dioxide (CO 2 ) gas; although the membrane separation method has simple equipment and low energy consumption, it is difficult to obtain high-purity CO 2 .

[0003] Aerogel, a nanoporous material with a three-dimensional skeleton structure, has attracted extensive attention from researchers in the fields of thermal insulation, adsorption separation, catalytic conversion, etc. due to its many excellent properties such as low density and high porosity, and is expected to be used for the adsorption of carbon dioxide. At present, aerogels are usually dried by supercritical drying, freeze drying, and vacuum drying during preparation. However, although these drying methods have relatively good drying effects, they require special equipment, and the investment and energy consumption are also high. Atmospheric pressure drying is a low-cost aerogel preparation method, but in practice, it is found that when water and solvent evaporate during atmospheric pressure drying, the pores of the aerogel are easily significantly shrunk, and then collapse and other structural degradation phenomena occur. Summary of the invention

[0004] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved method for preparing a carbon dioxide adsorbent material, which can significantly reduce the volume shrinkage of aerogel materials when drying at normal pressure, thereby facilitating lowering costs while achieving better adsorption performance.

[0005] The present invention also provides a carbon dioxide adsorbent material prepared by the method and its application in carbon dioxide capture.

[0006] In order to achieve the above object, a technical solution adopted by the present invention is:

[0007] A method for preparing a carbon dioxide adsorbent material, the method comprising:

[0008] (1) in the presence of a surfactant, allowing aminophenol and aldehyde to undergo a polycondensation reaction in a mixed system of alcohol and water, and adding an organic amine during the polycondensation reaction to react and prepare a modified phenolic resin sol;

[0009] (2) adding nano-oxides having surface hydroxyl groups to the modified phenolic resin sol, dispersing the nano-oxides uniformly, and aging the nano-oxides under heating conditions to prepare modified gels;

[0010] (3) subjecting the modified gel to solvent replacement in an aging solution to obtain an aged gel, and subjecting the aged gel to drying to obtain a carbon dioxide adsorbent.

[0011] In the present invention, aminophenol and aldehyde react, and hydrogen atoms at the ortho and para positions of the phenolic hydroxyl group and the carbonyl group of the aldehyde add to form hydroxyalkylphenol (the following hydroxyalkylphenol only exemplifies four possible reaction products), and the reaction route is roughly as follows;

[0012]

[0013] Then, the hydroxyalkylphenols are mutually dehydrated and condensed to form phenolic resin. The reaction system of the present invention is basically alkaline, so a phenolic resin with a network structure can be generated. Meanwhile, during the polycondensation reaction, an organic amine is added for modification, and the system is relatively alkaline. The organic amine can react with the hydroxyl group in the phenolic resin at least through the amino group contained therein. When the organic amine contains multiple amino groups, it can also participate in the formation of a cross-linked network structure during the formation of the phenolic resin, and finally form an organic amine-modified phenolic resin. The present invention is carried out in a mixed system of alcohol and water, and finally a sol can be obtained.

[0014] Furthermore, the present invention innovatively introduces surfactants in situ during the sol and gel formation process. On the one hand, it can reduce the surface tension of the solvent, regulate the gel network structure by directional adsorption, effectively inhibit the capillary stress in the subsequent drying process, and significantly reduce the volume shrinkage of the material; on the other hand, the addition of surfactants may adjust the reaction rate and product distribution by forming micelles or changing the reaction environment. The present invention can increase the amount of pore formation by adding surfactants.

[0015] At the same time, the present invention also adds nano oxides with surface hydroxyl groups during the gelation process. First, the nano oxides are anchored at the polymer network nodes in the sol-gel conversion stage, and their high specific surface area and surface hydroxyl groups can provide active sites for organic amine modification; at the same time, their surface hydroxyl groups also have the ability to react with phenolic resins, and can also form hydrogen bonds and other forces with hydroxyl groups on phenolic resins, thereby improving their stability in the system; second, the nano oxides can be embedded in the aerogel network as a rigid skeleton, and the pore structure can be stabilized by physical and chemical adsorption and bonding to further prevent collapse; third, the high modulus characteristics of the nano oxides can improve the compressive strength of the material, and its inherent adsorption capacity also gives the composite material an additional adsorption function;

[0016] The synergistic effect and multiple regulation of the above operations optimize the interpenetrating network configuration of the material, significantly improve the shrinkage phenomenon of the aerogel material during normal pressure drying, increase the specific surface area of ​​the material, increase the surface roughness, and the free amino groups on the material can serve as adsorption sites for carbon dioxide, so that carbon dioxide can be effectively captured in the form of carbamates, so that the material of the present invention can not only adopt low-cost normal pressure drying to reduce production costs, but also can obtain more ideal carbon dioxide adsorption performance.

[0017] According to some preferred aspects of the present invention, in step (3), the drying process includes normal pressure drying. Of course, the drying process can actually adopt other drying methods such as supercritical drying, freeze drying, etc., but these methods require special equipment and have high energy consumption. The present invention can adopt normal pressure drying with lower cost, and still ensure that the pore structure of the obtained aerogel material is well maintained and stable, and reduce the occurrence of adverse situations such as volume shrinkage. Therefore, it is preferred to adopt normal pressure drying.

[0018] In some embodiments of the present invention, in step (3), the treatment temperature of the drying treatment is controlled to be 25-105°C, for example, it can be 25-35°C, 40-50°C, 55-65°C, 70-80°C, 85-95°C, 100-105°C, etc.

[0019] In some embodiments of the present invention, in step (3), the drying time is controlled to be 1-3 days, about 24-72 hours.

[0020] According to some preferred aspects of the present invention, the surfactant has a structure shown in formula (I):

[0021] In formula (I), R 1 C 10-20 Straight chain alkyl, R 2 , R 3 , R 4 Independently for C 1-3 Alkyl, X is halogen.

[0022] Furthermore, R 1 is tetradecyl, pentadecyl, hexadecyl, heptadecyl or octadecyl, R 2 , R 3 , R 4 are independently selected from methyl, ethyl or propyl, and X is chlorine or bromine.

[0023] Furthermore, according to some preferred and specific aspects of the present invention, the surfactant is hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride.

[0024] In some embodiments of the present invention, the aminophenol is a combination of one or more selected from 4-aminophenol, 3-aminophenol, aminocatechol, aminoresorcinol, and aminohydroquinone.

[0025] In some embodiments of the present invention, the aldehyde C 1-20 Alkyl aldehyde. Further, the aldehyde includes but is not limited to a combination of one or more of formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, pentaldehyde, hexaldehyde and heptaldehyde.

[0026] In some embodiments of the present invention, the alcohol is a combination of one or more of ethanol, methanol and isopropanol.

[0027] In some embodiments of the present invention, the organic amine comprises a plurality of secondary amines and / or primary amines; further, the organic amine is a combination of one or more selected from polyethyleneimine (PEI), tetraethylenepentamine (TEPA) and pentaethylenehexamine (PEHA).

[0028] In some embodiments of the present invention, the aging liquid is a combination of one or more selected from ethanol, methanol, acetone, isopropanol, and n-hexane.

[0029] In some embodiments of the present invention, the nano-oxide having surface hydroxyl groups has a particle size of 14-200 nm and a specific surface area of ​​100-1000 m 2 / g. Further, the morphology of the nano-oxide with surface hydroxyl groups can be one or more of aerogel, gas phase, sphere, rod, sheet, and porous.

[0030] According to some preferred and specific aspects of the present invention, the nano-oxide having surface hydroxyl groups comprises silicon oxide, aluminum oxide or zirconium oxide, or a combination thereof.

[0031] According to some preferred and specific aspects of the present invention, the added amount of the nano-oxide having surface hydroxyl groups is 10%-65% of the total mass of the aminophenol, the aldehyde, the surfactant and the nano-oxide having surface hydroxyl groups, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc.

[0032] According to some preferred aspects of the present invention, the molar ratio of the aminophenol to the aldehyde is 1:0.5-2.5.

[0033] According to some preferred aspects of the present invention, the molar ratio of the aminophenol, the surfactant, the alcohol and the water is 1:0.1-0.5:20-80:10-30.

[0034] In some embodiments of the present invention, the molar ratio of the aminophenol, the aldehyde, the surfactant, the alcohol and the water is 1:0.5-2.5:0.1-0.5:20-80:10-30.

[0035] In some embodiments of the present invention, the molar ratio of the aminophenol, the aldehyde, the surfactant, the alcohol and the water is 1:1-2.5:0.1-0.5:20-80:10-30.

[0036] In some embodiments of the present invention, the molar ratio of the aminophenol, the aldehyde, the surfactant, the alcohol and the water is 1:0.5-1.0:0.1-0.5:40-80:10-20.

[0037] According to some preferred aspects of the present invention, the amount of the organic amine added is 10wt.%-80wt.% of the total mass of the aminophenol, the aldehyde and the surfactant, calculated by weight percentage. In some embodiments of the present invention, the amount of the organic amine added is 10wt.%-20wt.%, or 25wt.%-30wt.%, or 35wt.%-40wt.%, or 45wt.%-50wt.%, or 55wt.%-60wt.%, or 65wt.%-70wt.%, etc., calculated by weight percentage.

[0038] In some embodiments of the present invention, in step (1), the polycondensation reaction and the reaction are controlled to be carried out at -30 to 30° C. Further, in step (1), the polycondensation reaction and the reaction can be controlled to be carried out at -30 to 25° C., or at -30 to 10° C., or at -30 to 5° C., or at -20 to 0° C., or at -20 to -5° C.

[0039] In some embodiments of the present invention, in step (1), the organic amine is added within 20 minutes of the polycondensation reaction, for example, within 15 minutes, or within 10 minutes, further within 5-15 minutes, or within 8-12 minutes.

[0040] In some embodiments of the present invention, in step (2), the aging is controlled to be carried out at a temperature of 40-70°C.

[0041] In some embodiments of the present invention, in step (2), the aging time is controlled to be 0.5-2h.

[0042] In some embodiments of the present invention, in step (3), the solvent replacement is controlled to be carried out at 20-30°C.

[0043] In some embodiments of the present invention, in step (3), during the solvent replacement process, the volume ratio of the aging solution to the modified gel is controlled to be 1-50:1, and the aging solution is replaced every 1-24 hours.

[0044] In some embodiments of the present invention, in step (3), during the solvent replacement process, the volume ratio of the aging liquid to the modified gel is controlled to be 1-40:1, or 1-30:1, or 1-20:1, or 1-10:1, or 1-5:1, or 1-4:1, or 1-3:1, etc.

[0045] In some embodiments of the present invention, in step (3), the time for solvent replacement is 24-48 hours.

[0046] In some preferred embodiments of the present invention, the method for preparing the carbon dioxide adsorbent material comprises:

[0047] The aminophenol, aldehyde, surfactant, alcohol and water are mixed, stirred at -30°C to room temperature, and organic amine is added after stirring for 1-20 minutes, and stirring is continued to obtain a modified phenolic resin sol;

[0048] Adding nano-oxides with surface hydroxyl groups to the modified phenolic resin sol, stirring it evenly, pouring it into a molding mold, sealing it and placing it in an oven, waiting for it to completely gel and age until it can be demolded, to obtain a modified gel;

[0049] adding the modified gel into an aging solution, sealing, and performing solvent replacement to obtain an aged gel;

[0050] The aged gel is dried at normal pressure to obtain a carbon dioxide adsorbent material.

[0051] Another technical solution provided by the present invention is a carbon dioxide adsorbent material prepared by the above-mentioned method for preparing the carbon dioxide adsorbent material.

[0052] Another technical solution provided by the present invention is an application of the above-mentioned carbon dioxide adsorption material in carbon dioxide capture.

[0053] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0054] (1) The method of the present invention realizes dual regulation of the aerogel structure in the sol-gel process through the synergistic effect of the surfactant and the nano-oxide, and the shrinkage degree is controlled and the shrinkage rate is small, so that the gel can be dried by a low-cost atmospheric pressure drying method, especially the problem of structural collapse of the gel prepared by the existing method during atmospheric pressure drying can be avoided, which is conducive to large-scale industrial production;

[0055] (2) The density of the carbon dioxide adsorbent prepared by the method of the present invention is 0.09-0.35 g / cm 3 , with a specific surface area of ​​178.5-352.6m 2 / g, showing the characteristics of light weight, high strength and high specific surface area. 2 The adsorption capacity under volume concentration conditions is 2.1-4.2mmol / g, showing high efficiency and selective adsorption of carbon dioxide gas, which can be used as a flue gas CO 2 The adsorption material has good stability, simple preparation method and is suitable for industrial-scale production;

[0056] (3) Various carriers can be combined in the sol-gel conversion process, including but not limited to honeycomb fiber carriers, honeycomb ceramic carriers, etc., and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a physical picture of the carbon dioxide adsorbent material prepared in Example 1 of the present invention;

[0058] Figure 2 This is a comparison diagram of the sizes of the aged gels before and after drying in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0059] Figure 3 It is a comparison chart of the shrinkage rate of the aged gel before and after drying in Examples 1-6 of the present invention and Comparative Example 1-2. DETAILED DESCRIPTION

[0060] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0061] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0062] Example 1

[0063] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0064] 3-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride (CTAC), ethanol and water are mixed in a molar ratio of 1:2:0.5:80:10, stirred at 0°C for 10 minutes, then polyethyleneimine (molecular weight of about 600) accounting for 65wt.% of the total mass of 3-aminophenol, formaldehyde and hexadecyltrimethylammonium chloride is added, and stirring is continued for 10 minutes to obtain a modified phenolic resin sol; then, silica aerogel powder (purchased from Nano Technology Co., Ltd.) accounting for 65wt.% of the total mass of 3-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride and silica aerogel powder is added to the above-mentioned modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 50°C oven, after it is completely gelled and aged for 1 hour, demolded to obtain a modified gel. The modified gel was added to n-hexane for aging (the volume ratio of the modified gel to n-hexane was 1:1), sealed, aged at room temperature for 24 hours, and the n-hexane was replaced every 12 hours to obtain the aged gel; the sample was taken out and dried at normal pressure, the temperature program was: 25°C, and the drying time was 3 days (d represents days);

[0065] After drying, the carbon dioxide adsorption material (aerogel material, see Figure 1 Its density is 0.09g / cm 3 , shrinkage rate is 20%, BET specific surface area is 352.6m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 4.2mmol / g.

[0066] Shrinkage rate (%) = (1-aerogel diameter after drying / aerogel diameter after aging) × 100%.

[0067] The BET specific surface area was measured using a Micromeritics ASAP2020 specific surface area and pore distribution analyzer (Beijing Jin'ep Technology Co., Ltd.), and the samples were pretreated by degassing at 120 °C in a vacuum for 8 h.

[0068] At 50°C, 15% CO 2 The test method for adsorption under volume concentration conditions is as follows: the adsorbent is pretreated with nitrogen at 373K and then 15% CO is introduced at 323K. 2 The adsorption experiment was carried out by simulating flue gas (100mL / min). 2 The penetration curve is drawn based on the concentration change. Saturation is determined when the outlet and inlet concentrations are consistent. The adsorption amount is calculated by integrating the penetration curve with the intake parameters.

[0069] Example 2

[0070] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0071] 4-aminophenol, acetaldehyde, hexadecyltrimethylammonium bromide, ethanol and water are mixed in a molar ratio of 1:0.5:0.3:60:15, and stirred at 25°C for 15 minutes. Then, polyethyleneimine (molecular weight of about 600) accounting for 50wt.% of the total mass of 4-aminophenol, acetaldehyde and hexadecyltrimethylammonium bromide is added, and stirring is continued for 15 minutes to obtain a modified phenolic resin sol; then, fumed silicon oxide powder (purchased from Hubei Huifu Nanomaterial Co., Ltd., brand HL-45) accounting for 50wt.% of the total mass of 4-aminophenol, acetaldehyde, hexadecyltrimethylammonium bromide and fumed silicon oxide powder is added to the modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 60°C oven, after it is completely gelled and aged for 0.5h, demoulding, and a modified gel is obtained. The modified gel was added to methanol for aging (the volume ratio of the modified gel to methanol was 1:1.5), sealed, and aged at room temperature for 36 hours, with methanol replaced every 18 hours to obtain the aged gel; the sample was taken out and dried at normal pressure, and the temperature program was:

[0072] 25℃, drying time is 8h;

[0073] 50℃, drying time is 8h;

[0074] 105℃, drying time is 8h;

[0075] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 0.12g / cm 3 , shrinkage is 13.0%, BET specific surface area is 262.1m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 3.2mmol / g.

[0076] Example 3

[0077] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0078] 4-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride, ethanol and water are mixed in a molar ratio of 1:1:0.4:50:20, stirred at -10°C for 20 minutes, then pentaethylenehexamine accounting for 40wt.% of the total mass of 4-aminophenol, formaldehyde and hexadecyltrimethylammonium chloride is added, and stirring is continued for 10 minutes to obtain a modified phenolic resin sol; then a nano-oxide with surface hydroxyl groups accounting for 40wt.% of the total mass of 4-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride and the nano-oxide with surface hydroxyl groups (composed of fumed silicon oxide powder (purchased from Hubei Huifu Nanomaterial Co., Ltd., brand HL-45) and fumed aluminum oxide powder (purchased from Hubei Huifu Nanomaterial Co., Ltd., brand ALuna-100) in a mass ratio of 2:1) is added to the above-mentioned modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 40°C oven, aged for 2 hours after it is completely gelled, and demolded to obtain a modified gel. The modified gel was added to isopropanol for aging (the volume ratio of the modified gel to isopropanol was 1:2), sealed, aged at room temperature for 24 hours, and the isopropanol was replaced every 12 hours to obtain the aged gel; the sample was taken out and dried at normal pressure, and the temperature program was:

[0079] 25℃, drying time is 12h;

[0080] 60℃, drying time is 12h;

[0081] 105℃, drying time is 12h;

[0082] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 0.15g / cm 3 , shrinkage rate is 13.6%, BET specific surface area is 245.8m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 2.6mmol / g.

[0083] Example 4

[0084] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0085] 4-aminocatechol, propionaldehyde, hexadecyltrimethylammonium chloride, ethanol and water were mixed in a molar ratio of 1:1.5:0.2:40:25, stirred at -20°C for 10 minutes, then 20wt.% of tetraethylenepentamine accounting for the total mass of 4-aminocatechol, propionaldehyde and hexadecyltrimethylammonium chloride was added, and stirring was continued for 15 minutes to obtain a modified phenolic resin sol; then 4-aminocatechol, propionaldehyde, hexadecyltrimethylammonium chloride and a phenolic resin having surface hydroxyl groups were added. 30wt.% of the total mass of the nano-oxide with surface hydroxyl groups (composed of fumed silicon oxide (purchased from Hubei Huifu Nanomaterial Co., Ltd., brand HL-45) and fumed aluminum oxide powder (purchased from Hubei Huifu Nanomaterial Co., Ltd., brand ALuna-100) in a mass ratio of 3:1) is added to the above-mentioned modified phenolic resin sol, stirred evenly and poured into a molding mold, sealed and placed in a 60°C oven, after it is completely gelled and aged for 1h, demolded, and a modified gel is obtained. The modified gel is added to methanol for aging (the volume ratio of the modified gel to methanol is 1:3), sealed, aged at room temperature for 36h, and the methanol is replaced every 18h to obtain an aged gel; the sample is taken out and dried at normal pressure, and the temperature program is:

[0086] 25℃, drying time is 1d;

[0087] 50℃, drying time is 1d;

[0088] 105℃, drying time is 6h;

[0089] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 0.22g / cm 3 , shrinkage rate is 22.2%, BET specific surface area is 195.6m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 2.3mmol / g.

[0090] Example 5

[0091] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0092] 5-aminoresorcinol, butyraldehyde, hexadecyltrimethylammonium bromide, ethanol and water are mixed in a molar ratio of 1:2.5:0.1:20:30, and stirred at -30°C for 30 minutes. Then, polyethyleneimine (molecular weight of about 600) accounting for 10wt.% of the total mass of 5-aminoresorcinol, butyraldehyde and hexadecyltrimethylammonium bromide is added, and stirring is continued for 15 minutes to obtain a modified phenolic resin sol; then, fumed alumina powder (purchased from Hubei Huifu Nanomaterial Co., Ltd., brand ALuna-100) accounting for 10wt.% of the total mass of 5-aminoresorcinol, butyraldehyde, hexadecyltrimethylammonium bromide and fumed alumina powder is added to the above-mentioned modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 70°C oven, after it is completely gelled and aged for 0.5h, demolded to obtain a modified gel. The modified gel was added to ethanol for aging (the volume ratio of the modified gel to ethanol was 1:3), sealed, and aged at room temperature for 24 hours to obtain the aged gel; the sample was taken out and dried at normal pressure, and the temperature program was:

[0093] 25℃, drying time is 1d;

[0094] 60℃, drying time is 12h;

[0095] 105℃, drying time is 12h;

[0096] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 0.35g / cm 3 , shrinkage rate is 25.6%, BET specific surface area is 178.5m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 2.1mmol / g.

[0097] Example 6

[0098] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0099] 3-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride, ethanol and water are mixed in a molar ratio of 1:4:0.5:80:10, stirred at 0°C for 10 minutes, then polyethyleneimine (molecular weight of about 600) accounting for 65wt.% of the total mass of 3-aminophenol, formaldehyde and hexadecyltrimethylammonium chloride is added, and stirring is continued for 10 minutes to obtain a modified phenolic resin sol; then, silica aerogel powder (purchased from Nano Technology Co., Ltd.) accounting for 65wt.% of the total mass of 3-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride and silica aerogel powder is added to the above-mentioned modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 50°C oven, after it is completely gelled and aged for 1 hour, demolded to obtain a modified gel. The modified gel was added to n-hexane for aging (the volume ratio of the modified gel to n-hexane was 1:1), sealed, aged at room temperature for 24 hours, and the n-hexane was replaced every 12 hours to obtain the aged gel; the sample was taken out and dried at normal pressure, the temperature program was: 25°C, and the drying time was 3 days;

[0100] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 1.8g / cm 3 , shrinkage is 43.9%, BET specific surface area is 15.5m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 0.5mmol / g. This result shows that when the formaldehyde content is high, it may lead to a significant increase in the crosslinking degree of the reaction system, accelerate the hydroxymethylation and condensation reactions, and ultimately lead to excessive drying shrinkage.

[0101] Comparative Example 1

[0102] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0103] 3-aminophenol, formaldehyde, hexadecyltrimethylammonium bromide, ethanol and water are mixed in a molar ratio of 1:2:0.01:60:30, stirred at 0°C for 10 minutes, then 30wt.% of polyethyleneimine (molecular weight of about 600) accounting for the total mass of 3-aminophenol, formaldehyde and hexadecyltrimethylammonium bromide is added, and stirring is continued for 15 minutes to obtain a modified phenolic resin sol; then 30wt.% of silica aerogel powder (purchased from Nano Technology Co., Ltd.) accounting for the total mass of 3-aminophenol, formaldehyde, hexadecyltrimethylammonium bromide and silica aerogel powder is added to the above-mentioned modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 70°C oven, after it is completely gelled and aged for 3 hours, demolded to obtain a modified gel. The modified gel was added to n-hexane for aging (the volume ratio of the modified gel to n-hexane was 1:1), sealed, aged at room temperature for 24 hours, and the n-hexane was replaced every 12 hours to obtain the aged gel; the sample was taken out and dried at normal pressure, the temperature program was: 25°C, and the drying time was 3 days;

[0104] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 1.5g / cm 3 , shrinkage is 40.5%, BET specific surface area is 45.5m 2 / g, at 50℃, 15%CO 2 The adsorption amount under volume concentration conditions is 0.9mmol / g. This result shows that when the amount of surfactant added is very small, its regulatory effect on the system is limited and the volume shrinkage of the material cannot be reduced.

[0105] Comparative Example 2

[0106] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0107] 3-aminophenol, formaldehyde, hexadecyltrimethylammonium bromide, ethanol and water were mixed in a molar ratio of 1:2:0.01:60:30, stirred at 0°C for 10 minutes, then 30wt.% of polyethyleneimine (molecular weight of about 600) accounting for the total mass of 3-aminophenol, formaldehyde and hexadecyltrimethylammonium bromide was added, and stirring was continued for 15 minutes to obtain a modified phenolic resin sol; after stirring evenly, it was poured into a molding mold, sealed and placed in a 70°C oven, and after it was completely gelled and aged for 3 hours, demolded to obtain a gel. The modified gel was added to n-hexane for aging (the volume ratio of the modified gel to n-hexane was 1:1), sealed, aged at room temperature for 24 hours, and the n-hexane was replaced every 12 hours to obtain an aged gel; the sample was taken out and dried at normal pressure, and the temperature program was: 25°C, and the drying time was 3d;

[0108] After drying, the carbon dioxide adsorption material (aerogel material) is obtained, and its density is 1.7g / cm 3 , shrinkage is 46.3%, BET specific surface area is 10.5m 2 / g, at 50℃, 15%CO 2 The adsorption amount under the volume concentration condition is 0.3mmol / g. This result shows that the small amount of surfactant added and the absence of nano-oxide will cause the volume shrinkage of the material to increase significantly compared with the example.

[0109] See the comparison diagram of the size of the aged gel before and after drying in Example 1, Comparative Example 1 and Comparative Example 2. Figure 2 As shown, it can be clearly seen that the size of Comparative Examples 1 and 2 shrinks significantly before and after drying.

[0110] Further, the comparison of the shrinkage rates of the aged gels before and after drying in Examples 1-6 and Comparative Examples 1-2 is shown in Figure 3 As shown, it can be clearly seen that the shrinkage rate of the aged gel in Examples 1-5 of the present invention before and after drying is significantly suppressed compared with Example 6 and Comparative Examples 1-2; Example 6 added too much formaldehyde, resulting in excessive cross-linking, which in turn affected the final shrinkage rate.

[0111] Comparative Example 3

[0112] This example provides a method for preparing a carbon dioxide adsorbent material and the carbon dioxide adsorbent material prepared therefrom. The method for preparing the carbon dioxide adsorbent material comprises:

[0113] 3-Aminophenol, formaldehyde, hexadecyltrimethylammonium chloride (CTAC), ethanol and water were mixed in a molar ratio of 1:2:0.5:80:10, stirred at 0°C for 1 hour, then added with polyethyleneimine (molecular weight of about 600) accounting for 65wt.% of the total mass of 3-aminophenol, formaldehyde and hexadecyltrimethylammonium chloride, and continued to stir for 10 minutes to obtain a modified phenolic resin sol; then, silica aerogel powder (purchased from Nano Technology Co., Ltd.) accounting for 65wt.% of the total mass of 3-aminophenol, formaldehyde, hexadecyltrimethylammonium chloride and silica aerogel powder was added to the modified phenolic resin sol, stirred evenly, poured into a molding mold, sealed and placed in a 50°C oven, no gel was formed, and a yellow precipitate appeared after standing for a period of time.

[0114] The reason for the above results is believed to be the combined effects of the condensation reaction, oxidation reaction and side reactions of 3-aminophenol and formaldehyde, which lead to the accumulation and precipitation of polymers and oxidation products without the formation of gel.

[0115] At the same time, the above results show that adding organic amine after the polycondensation reaction is basically completed has no effect and the expected product cannot be obtained.

[0116] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0117] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing a carbon dioxide adsorbent material, characterized in that: The preparation method comprises: (1) in the presence of a surfactant, allowing aminophenol and aldehyde to undergo a polycondensation reaction in a mixed system of alcohol and water, and adding an organic amine during the polycondensation reaction to react and prepare a modified phenolic resin sol; (2) adding nano-oxides having surface hydroxyl groups to the modified phenolic resin sol, dispersing the nano-oxides uniformly, and aging the nano-oxides under heating conditions to prepare modified gels; (3) subjecting the modified gel to solvent replacement in an aging solution to obtain an aged gel, and subjecting the aged gel to drying to obtain a carbon dioxide adsorbent.

2. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: In step (3), the drying treatment includes normal pressure drying; and / or, in step (3), the treatment temperature of the drying treatment is controlled to be 25-105°C.

3. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: The surfactant has a structure shown in formula (I): In formula (I), R1 is C 10-20 Straight chain alkyl, R2, R3, R4 are independently C 1-3 Alkyl, X is halogen; Further, R1 is tetradecyl, pentadecyl, hexadecyl, heptadecyl or octadecyl, R2, R3, R4 are independently selected from methyl, ethyl or propyl, and X is chlorine or bromine.

4. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: The aminophenol is a combination of one or more selected from 4-aminophenol, 3-aminophenol, aminocatechol, aminoresorcinol, and aminohydroquinone; and / or the aldehyde C 1-20 Alkyl aldehyde; and / or, the alcohol is a combination of one or more of ethanol, methanol and isopropanol; and / or, the organic amine comprises a plurality of secondary amines and / or primary amines; and / or, the aging solution is a combination of one or more selected from ethanol, methanol, acetone, isopropanol and n-hexane; and / or, the nano-oxide having surface hydroxyl groups has a particle size of 14-200 nm and a specific surface area of ​​100-1000 m 2 / g.

5. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: The surfactant is hexadecyltrimethylammonium bromide and / or hexadecyltrimethylammonium chloride; and / or, the nano-oxide with surface hydroxyl groups includes silicon oxide, aluminum oxide or zirconium oxide; and / or, in terms of mass percentage, the added amount of the nano-oxide with surface hydroxyl groups is 10%-65% of the total mass of the aminophenol, the aldehyde, the surfactant and the nano-oxide with surface hydroxyl groups.

6. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: The molar ratio of the aminophenol to the aldehyde is 1:0.5-2.5; and / or, the molar ratio of the aminophenol, the surfactant, the alcohol and the water is 1:0.1-0.5:20-80:10-30; and / or, in terms of weight percentage, the amount of the organic amine added accounts for 10wt.%-80wt.% of the total mass of the aminophenol, the aldehyde and the surfactant; and / or, the organic amine is a combination of one or more selected from polyethyleneimine, tetraethylenepentamine and pentaethylenehexamine.

7. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: In step (1), the polycondensation reaction and the reaction are controlled to be carried out at -30 to 30°C respectively; and / or, in step (1), the organic amine is controlled to be added within 20 minutes of the polycondensation reaction; and / or, in step (2), the aging is controlled to be carried out at a temperature of 40-70°C; and / or, in step (2), the aging time is controlled to be 0.5-2h; and / or, in step (3), the solvent replacement is controlled to be carried out at 20-30°C; and / or, in step (3), during the solvent replacement process, the volume ratio of the aging solution to the modified gel is controlled to be 1-50:1, and the aging solution is replaced every 1-24h.

8. The method for preparing a carbon dioxide adsorbent material according to claim 1, characterized in that: The method for preparing the carbon dioxide adsorbent material comprises: The aminophenol, aldehyde, surfactant, alcohol and water are mixed, stirred at -30°C to room temperature, and organic amine is added after stirring for 1-20 minutes, and stirring is continued to obtain a modified phenolic resin sol; Adding nano-oxides with surface hydroxyl groups to the modified phenolic resin sol, stirring it evenly, pouring it into a molding mold, sealing it and placing it in an oven, waiting for it to completely gel and age until it can be demolded, to obtain a modified gel; adding the modified gel into an aging solution, sealing, and performing solvent replacement to obtain an aged gel; The aged gel is dried at normal pressure to obtain a carbon dioxide adsorbent material.

9. A carbon dioxide adsorbent material prepared by the method for preparing a carbon dioxide adsorbent material according to any one of claims 1 to 8.

10. Use of the carbon dioxide adsorbent material according to claim 9 in capturing carbon dioxide.

Citation Information

Cited By

  • Carbon dioxide adsorption material as well as preparation method and application thereof

    CN120790085A